2002
DOI: 10.1007/s00104-001-0419-8
|View full text |Cite
|
Sign up to set email alerts
|

“Multimediale Symposiumsware”Eine Bereicherung der Aus- und Weiterbildung?

Abstract: The continual development of the internet has supported the spread of surgical knowledge by electronic means. High quality products have to be offered from a software as well as a contents point of view. The question as to whether these new media and their contents have a real value for efficient and motivating use in medical education needed to be answered by first assessing a quality profile for the development of surgical educational modules which were then evaluated on the basis of so-called "symposia ware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(19 reference statements)
0
1
0
2
Order By: Relevance
“…6,8,27,28 Recent surveys show that physicians are most likely to use the Internet to obtain medical information related to a specific question related to a specific clinical case, and seem to learn best when looking for the answer to a clinical question that arises from actual practice. 4,6,21 An illustration of this can be found in a recent study that reported that physicians’ likelihood of enrollment in a multicomponent Internet CME course to improve chlamydia screening increased with the number of at-risk women in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,27,28 Recent surveys show that physicians are most likely to use the Internet to obtain medical information related to a specific question related to a specific clinical case, and seem to learn best when looking for the answer to a clinical question that arises from actual practice. 4,6,21 An illustration of this can be found in a recent study that reported that physicians’ likelihood of enrollment in a multicomponent Internet CME course to improve chlamydia screening increased with the number of at-risk women in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…Zudem haben die Multimediaapplikationen einen höheren Wirkungsgrad [1,13] als die traditionellen Weiterbildungsmaßnahmen, was die tatsächliche und dauerhafte Vermittlung von medizinischen Inhalten anbelangt [9,10]. Dies ist durch die höhere Einprägsamkeit aufgrund der Verknüpfung akustischer und visueller Informationen bedingt, wie durch den Einsatz bewegter Bilder im Sinne von Videos und Animationen [5,19]. Darüber hinaus ist es heute durch die Weiterentwicklung einer verbesserten Software und einer leistungsstarken Hardware möglich, einen weiteren entscheidenden Vorteil der Multimediatechniken gegenüber den konventionellen Lehrmitteln optimal zu nutzen: die Interaktivität.…”
Section: Diskussionunclassified
“…Dies gelingt umso besser, je mehr Wahlmöglichkei-ten dem Studenten bei der Fallbearbeitung geboten werden. Im Vergleich zum konventionellen Lehrbuch bieten digitale Medien außerdem einen hohen Anschaulichkeitsgrad durch die Integration von Graphiken, Audio-und Videosequenzen, Animationen und Simulationen und erzielen dadurch eine besonders effiziente Wissensvermittlung [5,7]. Derzeit werden computergestützte Informationssysteme bereits für die Abbildung von Lexika, Lehrbüchern [16,18] Background and Purpose: Computer-assisted teaching and learning tools offer new opportunities for improving education and training of medical professionals.…”
unclassified